Structural elucidation of NASICON (Na3Al2P3O12) based glass electrolyte materials: effective influence of boron and gallium. Issue 26 (17th April 2018) - Allu, Amarnath R.; Balaji, Sathravada; Illath, Kavya; Hareendran, Chaithanya; Ajithkumar, T. G.; Biswas, Kaushik; Annapurna, K.
Abstract : Understanding the conductivity variations induced by compositional changes in sodium super ionic conducting (NASICON) glass materials is highly relevant for applications such as solid electrolytes for sodium (Na) ion batteries. Abstract : Understanding the conductivity variations induced by compositional changes in sodium super ionic conducting (NASICON) glass materials is highly relevant for applications such as solid electrolytes for sodium (Na) ion batteries. In the research reported in this paper, NASICON-based NCAP glass (Na2.8 Ca0.1 Al2 P3 O12 ) was selected as the parent glass. The present study demonstrates the changes in the Na + ion conductivity of NCAP bulk glass with the substitution of boron (NCABP: Na2.8 Ca0.1 Al2 B0.5 P2.7 O12 ) and gallium (NCAGP: Na2.8 Ca0.1 Al2 Ga0.5 P2.7 O12 ) for phosphorus and the resulting structural variations found in the glass network. For a detailed structural analysis of NCAP, NCABP and NCAGP glasses, micro-Raman and magic angle spinning-nuclear magnetic resonance (MAS-NMR) spectroscopic techniques (for 31 P, 27 Al, 23 Na, 11 B and 71 Ga nuclei) were used. The Raman spectrum revealed that the NCAP glass structure is more analogous to the AlPO4 mesoporous glass structure. The 31 P MAS-NMR spectrum illustrated that the NCAP glass structure consists of a high concentration of Q 0 (3Al) units, followed by Q 0 (2Al) units. The 27 Al MAS-NMR spectrum indicates that alumina exists at five different sites, which include AlO4 units surrounded by AlO6 units, Al(OP)4, Al(OP)5, Al(OAl)6 and Al(OP)6, in the NCAP glass structure. The 31 P, 27 Al and 11 B MAS-NMR spectra of the NCABP glass revealed the absence of B–O–Al linkages and the presence of B3 –O–B4 –O–P4 linkages which further leads to the formation of borate and borophosphate domains. The 71 Ga MAS-NMR spectrum suggests that gallium cations in the NCAGP glass compete with the alumina cations and occupy four (GaO4 ), five (GaO5 ) and six (GaO6 ) coordinated sites. The Raman spectrum of NCAGP glass indicates that sodium cations have also been substituted by gallium cations in the NCAP glass structure. From impedance analysis, the dc conductivity of the NCAP glass (∼3.13 × 10 −8 S cm −1 ) is slightly decreased with the substitution of gallium (∼2.27 × 10 −8 S cm −1 ) but considerably decreased with the substitution of boron (∼1.46 × 10 −8 S cm −1 ). The variation in the conductivity values are described based on the structural changes of NCAP glass with the substitution of gallium and boron.